Immediate one-stage breast reconstruction for an 85-year-old breast cancer patient using deep inferior epigastric perforator flap surgery. Issue 7 (10th July 2021) - Matsui, Koshi; Satake, Toshihiko; Araki, Misato; Kanaya, Emi; Igarashi, Takamichi; Okamoto, Maki; Miwa, Takeshi; Hirano, Katsuhisa; Watanabe, Toru; Sekine, Shinichi; Shibuya, Kazuto; Hashimoto, Isaya; et al.
Abstract: The deep inferior epigastric perforator (DIEP) flap is widely recognized as safe for use as a first-choice option in autologous tissue breast reconstruction; however, DIEP is often not performed for breast reconstruction in the elderly. We report a case of an 85-year-old woman who underwent DIEP flap reconstruction. Immediate reconstruction was performed after mastectomy. The patient successfully underwent DIEP flap reconstruction with no complications. Other options for reconstruction include a latissimus dorsi flap, a transverse rectus abdominis flap and implant-based reconstruction. DIEP flap reconstruction was performed, which does not cause muscle damage and provides sufficient volume. To our knowledge, this study is the first to report DIEP breast reconstruction in a patient over 85 years of age. This case demonstrates the usefulness of DIEP flap reconstruction for elderly patients.